Meeting Questions (2011)
Why does planet Earth change?, how does the internet work?, Why are there wars?, How do planes fly?, Why are there rich and poor?, How does the brain work?, Why does music exist? These are some of the questions that are developed in the workshops of the first stage of the University of Children EAFIT.